Low CD46 expression on activated CD4+ T cells predict improved Th1 cell reactivity to calcitriol in majority of patients with allergic eosinophilic asthma and healthy donors - Stichova, Julie; Slanina, Peter; Chovancova, Zita; Baros, Jan; Litzman, Marek; Litzman, Jiri; Vlkova, Marcela (Frontiers in Allergy, 2024)
BackgroundPrevious research showed that the intracellular complement system, with CD46 as its central molecule, regulates the Th1 response associated with IFN-γ production and transition to a type 1 regulatory response (Tr1) characterized by IL-10 production. This transition can be influenced by a vitamin D (calcitriol), favouring a shift towards Tr1 cells and increased IL-10 production, as described in some autoimmune diseases.ObjectiveIt is unknown whether calcitriol modulates CD46-induced Th1 response towards regulatory type 1 T cells (Tr1) in allergic eosinophilic asthma and its value in relation to reducing inflammatory response.MethodsCD4+ T cells from 58 patients with allergic eosinophilic asthma (AEA) and 49 healthy donors (HDs) were stimulated with αCD3/αCD46/IL-2 or αCD3/αCD46/IL-2/Calcitriol in vitro for 60 h and analyzed by flow cytometry. IFN-γ and IL-10 levels in cell culture supernatants were measured using ELISA.ResultsCD4+ T cells from patients with AEA demonstrated elevated CD46 expression in both the non-activated state and under stimulation conditions with αCD3/αCD46/IL-2 or αCD3/αCD46/IL-2/Calcitriol. Moreover, CD46 expression in AEA patients fluctuated with the pollen season, showing a significant increase during period of low pollen exposure. Calcitriol further induced CD4+Tr1 cells from in vitro generated CD4+Th1 cells in both HDs and AEA patients. However, in both cohorts were individuals (HDs: 35/49, AEA: 40/58) who responded to calcitriol with a more pronounced regulatory response. The calcitriol-induced regulatory effect manifested by a stronger surface decrease of CD46 on activated CD4+ T cells (by 40% in HDs and by 26% in AEA), accompanied by a significant inhibition of IFN-γ and increased IL-10 production (by 31% in HDs and by 85% in AEA). These individuals were termed as the CD46D group. Contrary to this, calcitriol induced an increase in CD46 expression at the CD4+ T cell surface in a minor group of HDs (14/49), and AEA patients (18/58), who were termed as the CD46I group. In CD46I group, CD4+ T cells produced less IFN-γ in comparison with CD46D group (by 33% in HDs and by 43% in AEA) and were unable to upregulate IL-10 production following stimulation with αCD3/αCD46/IL-2/Calcitriol.ConclusionOur results suggest the potential existence of a key for stratifying individuals suitable for calcitriol treatment in the context of low serum vitamin D levels. After validation in clinical studies, this key could be used as an adjunctive therapy not only for patients with allergic eosinophilic asthma, but also for other diseases.